2011
DOI: 10.1177/0269216311398699
|View full text |Cite
|
Sign up to set email alerts
|

Exploring access to rehabilitation services from allied health professionals for patients with primary high-grade brain tumours

Abstract: Primary brain tumours account for less than 2% of cancer diagnoses in the UK but more people under 40 die from a brain tumour than from any other cancer. Despite developments in some treatment options, survival remains poor and patients suffer with considerable functional and cognitive deficits. Rehabilitation for patients with primary brain tumours produces statistically and clinically significant improvements in function. When compared, similar functional gains are made following rehabilitation for brain tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
(37 reference statements)
3
24
0
Order By: Relevance
“…The results of this study support previous work which has shown that a lack of self-awareness, problem-solving skills, or decision-making abilities among patients with brain tumors may limit their ability to recognise their own needs, or to present themselves as better functioning than is actually the case [45,46]. In this study, patients reported being unable to recognise or articulate their own needs, or recall the support services available to address them, which acted as barriers that prevented them getting help.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study support previous work which has shown that a lack of self-awareness, problem-solving skills, or decision-making abilities among patients with brain tumors may limit their ability to recognise their own needs, or to present themselves as better functioning than is actually the case [45,46]. In this study, patients reported being unable to recognise or articulate their own needs, or recall the support services available to address them, which acted as barriers that prevented them getting help.…”
Section: Discussionsupporting
confidence: 88%
“…Given these inabilities, clinicians may need to take a greater role in assessing patients' needs and putting plans in place to ensure they receive support. Despite this, some evidence suggests poorer referral processes for this patient group, at least in the area of rehabilitation [45][46][47]. Low referral rates in the presence of problems seem to stem from clinicians' limited knowledge of the benefits of allied health services [45], discomfort discussing brain tumors and their prognosis [47], and beliefs that rehabilitation is not beneficial for persons with poor prognosis [22,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once adults are aware of the services available, they become more likely to use them again. The literature on cancer rehabilitation commonly reports physician unawareness of occupational therapy and poor communication among fields as barriers to use because a referral is needed for access to care (Cheville, 2005;McCartney, Butler, & Acreman, 2011). Possibly, physicians (or nurse practitioners) who are aware of occupational therapy are more likely to refer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients become dependent on caregivers for transportation when they lose their driver's license due to seizures. Limitations like this affect the patients' likelihood of and ability to participate in general rehabilitation programmes (McCartney et al, 2011), which may result in health disadvantages for the HGG population. An Internet-based intervention (IBI) may be an alternative for patients too challenged to participate in traditional faceto-face programmes (Forducey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%